Electrocatalytic oxidation of ethanol at silver chloride/ bromide modified carbon paste electrodes - Karim-Nezhad,Ghasem (2016)
Silver chloride modified carbon paste electrode was prepared as a new electrode and used to electrocatalytic oxidation of ethanol. For the first time, the catalytic oxidation of ethanol was demonstrated by cyclic voltammetry, chronoamperometry and amperometry methods at the surface of this modified carbon paste electrode. Compared to silver chloride modified carbon paste electrode, silver bromide modified carbon paste electrode and bare silver electrode catalysts, silver chloride modified carbon paste electrode exhibited markedly superior catalytic activity for the electrocatalytic oxidation of ethanol. It can be seen that the electrocatalytic efficiency of silver chloride modified carbon paste electrode is higher than the silver bromide modified carbon paste and bare silver electrodes. The catalytic oxidation peak current was linearly dependent on the ethanol concentration. The j0 for silver chloride modified carbon paste and silver bromide modified carbon paste electrodes are 11.2 and 5.4 folds respectively higher than that of the bare silver electrode. For silver chloride modified carbon paste electrode, the charge transfer coefficient (α), the number of electrons involved in the rate determining step (nα) and exchange current density (j0) were calculated as 0.46, 1 and 5.05×10-7 respectively. The modified electrode possesses high selectivity, good reproducibility and well stability.